Analisis Pelaksanaan Pemeriksaan Pajak pada Masa Pandemi Covid 19 di KPP Pratama Makassar Utara - Wulandari H, Magvira; Afifah, Nurul; Sari, Sri (Income Journal: Accounting, Management and Economic Research, 2023)
The purpose of this study is to determine the mechanism for implementing tax inspections during the Covid-19 pandemic at KPP Pratama North Makassar, to determine the effectiveness of the implementation of tax inspections based on the completion of SP2, and to find out the effectiveness of the implementation of tax inspections based on tax revenues. This research uses a qualitative approach. The results showed that the mechanism for implementing tax inspections during the Covid-19 pandemic was a meeting with taxpayers when the examination process was carried out online, The effectiveness of the implementation of the examination based on the completion of SP2 in 2020-2021 is included in the very effective criteria, and the effectiveness of the implementation of tax inspections based on tax inspection receipts is included in the very effective criteria. The implementation of tax inspections is carried out through the completion of SP2 as well as efforts to optimize the preparation and implementation of examinations by implementing an audit focus